Refugee Education 4.0: The Potential and Pitfalls of EdTech for Refugee Education - Sultan Al Habsi; Britta Rude (CESifo Forum, 2021)
The pandemic has led to a spike in implementing education technologies around the globe. Now the educational sector might finally catch up with technological advancements in other industries. Do new technologies in the area of learning have the potential to achieve a more equitable education distribution and include population groups with low access rates? Refugees are especially vulnerable with only 1 out of 4 refugee children enrolled in secondary education. Their educational paths are often disrupted and marked by a lack of systematic approaches. The potential of EdTech for refugee education is large but marked by several pitfalls. A low digital infrastructure as well as a lack of digital skills are challenges, in addition to the need for tailored educational offers and more sustainable approaches.
Keywords: 330